Pro-Cons of Sea Alms Traditions in the Perspective of Religion and Culture - Fatma Sari (Kaunia: Integration and Interconnection Islam and Science, 2017)
Sea alms (Nyadran) is a tradition that is carried out once a year in the coastal communities of the island of Java. The traditional process includes giving (Sesaji) to Nyi Roro Kidul. In the religious perspective, this is strictly prohibited, but this tradition has become an Indonesian cultural identity. This study will discuss the Sea Alms Tradition in perspective of religion and culture using literature study method.